Improving Students’ Ability in Writing Procedure Text through Broken Triangle/ Square/ Heart Model (A Classroom Action research at SMA 2 Peusangan) - Misnar Misnar; Mardiana Mardiana (Jurnal Pendidikan Almuslim, 2016)
This research explained about “Improving Students’ Ability in Writing Procedure Text Trough Broken Triangle/Square/Heart Model (A Classroom Action Research at SMA N 2 Peusangan)”. In fact, in real conditions most of the students could not write well. Such as the students had difficulties in finding some ideas, students were not able to write a good paragraph, the students had low motivation in writing. This researcher was Classroom Action Research . The data were analyzed through descriptive qualitative and quantitative research. This research was conducted at SMA N 2 Peusangan, Bireuen regency. The research subject was the first grade students of class X/1. In the first cycle, the action has not been successful and did not reach the criteria of success specified. The shortcoming in this cycle was the students did not manage the time well in doing the activity of writing procedure text; some of the students were still unmotivated and confused in writing procedure text. So, the researcher continued to the second cycle by improving the shortcoming in the first cycle. After the researcher did all steps of action research (cycle 1 and cycle 2) the students’ mean score increased from 64 in the first cycle, and became 72 in the second cycle. Furthermore, based on the result of questionnaire 82% students were motivated to learn procedure text. In addition, the researcher concluded that broken triangle/square/heart model had improved students’ ability and motivated them in writing procedure text. Key words: Writing Procedure Text, and Broken Triangle/Square/Heart Model.